Occurrence, fate, and fluxes of perfluorochemicals (PFCs) in an urban catchment : Marina reservoir, Singapore - Nguyen, Viet Tung (2013)
A study was carried out to characterize the occurrence, sources and sinks of perfluorochemicals (PFCs) in the Marina Catchment and Reservoir, Singapore. Salinity depth profiles indicated the reservoir was stratified with lower layers consisting of sea water (salinity ranging from 32 to 35 g L−1) and a brackish surface layer containing approximately 14–65% seawater. The PFC mixture detected in catchment waters contained perfluoroalkyl carboxylates (PFCAs), particularly perfluorooctanoate (PFOA), perfluorohexanoate (PFHpA), perfluorooctane sulfonate (PFOS) and PFC transformation products. PFC concentrations in storm runoff were generally higher than those in dry weather flow of canals and rivers. PFC concentration profiles measured during storm events indicated ‘first flush’ behavior, probably because storm water is leaching PFC compounds from non-point sources present in the catchment area. Storm runoff carries high concentrations of suspended solids (SS), which suggests that PFC transport is via SS. In Marina Bay, PFCs are deposited in the sediments along with the SS. In sediments, the total PFC concentration was 4,700 ng kg−1, approximately 200 times higher than in the bottom water layers. Total perfluoroalkyl sulfonates (PFSAs), particularly PFOS and 6:2 fluoro telomer sulfonate (6:2 FtS) were dominant PFCs in the sediments. PFC sorption by sediments varied with perfluorocarbon chain length, type of functional group and sediment characteristics. A first approximation analysis based on SS transport suggested that the annual PFC input into the reservoir was approximately 35 ± 12 kg y−1. Contributions of SS, dry weather flow of river/canals, and rainfall were approximately 70, 25 and 5%, respectively. This information will be useful for improving strategies to protect the reservoir from PFC contamination.